Replacement of Missing Anterior Teeth in a Patient with Temporomandibular Disorder - Satheesh B. Haralur; Omar Saeed Al-Shahrani (Case Reports in Dentistry)
The loss of anterior teeth leads to extreme psychological trauma, along with functional and esthetic debilitations. Healthy anterior teeth play an important role of protecting the posterior teeth during excursive mandibular movement. Loss of anterior teeth induces posterior interference with extended disocclusion time. Posterior disocclusion is critical to remove the harmful force on the teeth temporomandibular joint and eliminate muscle hypertonicity. Occlusal interference is considered as contributing factor to temporomandibular disorder (TMD) symptoms. Prosthesis design should eliminate deleterious tooth contacts. Establishing optimum anterior guidance is a key to establishing harmonious functional occlusion in addition to the correction of the esthetic and phonetic disabilities. This case report explains the steps involved in the rehabilitation of the TMD patient with loss of maxillary anterior teeth.